Multi-robot odor-plume tracing in indoor natural airflow environments using an improved ACO algorithm - Qing-Hao Meng; Wei-Xing Yang; Yang Wang; Ming Zeng (2010 IEEE International Conference on Robotics and Biomimetics, 2010)
We consider odor-plume tracing using a multi-robot system in indoor natural airflow environments. The purpose of odor-plume tracing is to approach the odor source via following the found plume with mobile robot(s). Owing to the chaotic nature of the odor transport in the atmosphere, tracing the resultant patchy meandering plume down to its source is thus not a trivial task. A novel multi-robot based plume tracing method is proposed. When the plume is found, multiple robots are coordinated to trace the time-variant plume by an improved ant colony optimization (ACO) algorithm combined with upwind search. The results of experiments compared with the spiral surge approach using real robots in indoor natural airflow environments validate the feasibility and robustness of the proposed plume tracing method.